2015
DOI: 10.4172/2161-069x.1000346
|View full text |Cite
|
Sign up to set email alerts
|

Patients Diagnosed with Colorectal Cancer in Rural Areas in Arizona Typically Present with Higher Stage Disease

Abstract: Background Despite the decreasing incidence of colorectal cancer (CRC) over the past three decades disparities remain in its incidence, stage at presentation, and efficiency of staging and treatment between different communities, particularly when comparing urban and rural areas. The aim of the study was to assess disparities that exist in CRC outcomes among urban, international border counties, and non-border counties in Arizona. Methods A retrospective analysis of CRC data from the Arizona Cancer Registry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…58 An urban residence was a significant risk factor for CRC (OR=1.95). 59 Individuals in rural areas are more likely to come with a higher stage of CRC. This could be a result of a lack of appropriate access to health care, a lack of awareness, poor education, and a paucity of specialists.…”
Section: Discussionmentioning
confidence: 99%
“…58 An urban residence was a significant risk factor for CRC (OR=1.95). 59 Individuals in rural areas are more likely to come with a higher stage of CRC. This could be a result of a lack of appropriate access to health care, a lack of awareness, poor education, and a paucity of specialists.…”
Section: Discussionmentioning
confidence: 99%
“…Two upregulated lncRNAs (HOTAIR and UCA1) and two downregulated lncRNAs (LOH12CR2 and PART1) were common between the microarray, CRN and circlncRNAnet results. Several studies have previously reported that HOTAIR is an oncogene that plays a crucial role in the progression of various types of cancer (20), including gastric cancer (21,22), lung cancer (23), colorectal cancer (24), liver cancer (25), gallbladder cancer (26), breast cancer (27), cervical cancer (28), ovarian cancer (29), and prostate cancer (30). The oncogene UCA1 is known to be involved in various types of cancer, such as gastric cancer (31), breast cancer (32), bladder cancer (33) and colorectal cancer (34).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patient and hospital characteristics, which were controlled for in this analysis, are significant contributors to surgical outcomes. For example, even if surgical technical expertise is equivalent among surgeons performing colorectal cancer surgery, factors such as decreased access to subspecialists for multidisciplinary cancer care and more advanced disease at presentation as a result of delayed diagnosis may result in worsened colorectal cancer outcomes in small and/or rural hospitals (ie, those with a higher proportion of NUBR surgeons).…”
mentioning
confidence: 99%